Network congestion control methods and theory. (2015) - Wu, Wei; Du, Wencai; Ruan, Guolong
Network congestion tends to be more complicated owing to the massive growth of wired and wireless network users, services and deficiency of transmission capacity. This paper introduces the latest research on TCP/IP network congestion and control theory related to congestion control, analyses different characteristics and control methods; current challenges and future research directions are also discussed.